Ashwagandha and Chronic Stress: A Review of Its Neuroimmune Modulatory Potential - Assyfa Ulti Iskandar; Retno Pudji Rahayu; Anwar Ma'ruf; Theresia Indah Budhy (Smart Medical Journal, 2025)
Introduction: Chronic stress disrupts neuroimmune homeostasis, driving neuroinflammation and neuronal damage. Despite growing interest in natural interventions, comprehensive reviews on ashwagandha’s dual neuro-immunomodulatory mechanisms remain limited. This review examines ashwagandha’s potential in mitigating chronic stress-induced neuroimmune dysregulation.Methods: A review was conducted by searching PubMed, Scopus, and Google Scholar for relevant preclinical and clinical studies published between 2015 and 2025. Studies were selected based on their focus on Ashwagandha’s effects on the hypothalamic–pituitary–adrenal (HPA) axis, cytokine expression, oxidative stress, and neuroprotection. Data were extracted and synthesized thematically.Results: Ashwagandha was found to downregulate pro-inflammatory cytokines (TNF-α, IL-6), inhibit NF-κB signaling, and enhance antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT). Clinical and animal studies reported cortisol reduction, attenuation of microglial activation, increased brain-derived neurotrophic factor (BDNF) levels, improved T-cell proliferation and NK cell activity, and restoration of Th1/Th2 balance. These mechanisms were associated with improved mood, cognition, and stress resilience.Conclusion: Ashwagandha demonstrates multimodal neuroimmune modulation, offering a promising natural therapeutic for stress-related disorders. Standardized extracts warrant further investigation for clinical translation.